2016
DOI: 10.4238/gmr.15017396
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic mimicry and hypoxia-inducible factor-1α expression in cervical squamous cell carcinoma

Abstract: ABSTRACT. In this study, the existence of vasculogenic mimicry (VM) in cervical squamous cell carcinoma was investigated. To this end, the relationship between hypoxia-inducible factor 1α (HIF-1α) and the development, infiltration, and metastasis of cervical squamous cell carcinoma was studied. Between January 2010 and December 2010, 67 human cervical squamous carcinoma tissue samples were collected and stained by CD34/periodic acid-Schiff double staining to detect the existence of VM. HIF-1α expression was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Thus, the jury is still out on whether all “pattern structures” can be classified as VM. A further problem in the reporting of the presence of VM occurs when no imagery is shown; without physical evidence it is difficult to draw conclusions (27). Similarly, small images in black and white do not allow the reader to be convinced of the presence of PAS+/CD31– structures (28).…”
Section: Is the Combination Of Pas+ And Absence Of Ec Markers A Definmentioning
confidence: 99%
“…Thus, the jury is still out on whether all “pattern structures” can be classified as VM. A further problem in the reporting of the presence of VM occurs when no imagery is shown; without physical evidence it is difficult to draw conclusions (27). Similarly, small images in black and white do not allow the reader to be convinced of the presence of PAS+/CD31– structures (28).…”
Section: Is the Combination Of Pas+ And Absence Of Ec Markers A Definmentioning
confidence: 99%
“…For instance in a mouse model of melanoma, mice in the ischemic model group were found to demonstrate increased VM compared to the control group, which was positively correlated with HIF-1α and HIF-2α expression, indicating that oxygen deficiency promoted VM [12]. Further, a large number of studies have shown that hypoxia or HIF molecules promote the VM process in multiple tumor types including cervical cancer [13], small cell lung cancer [14], liver cancer [15], and gallbladder cancer [16]. HIF-1 can also directly regulate the expression of multiple VM-related molecules such as VEGF, Twist, LOX, MMP2, and MIFect [17].…”
Section: Main Textmentioning
confidence: 99%
“…PAS + structures have been suggested to cross over true blood vessels containing RBCs, and cancer cells can secrete copious amounts of PAS + mucoproteins, but this should not necessarily imply vessel formation. Electron microscopy studies have not shown blood components inside VM channels in some studies, and many studies have failed to provide adequate imaging evidence of VM [ 153 , 154 ]. These findings have raised scepticism about the methods used to identify VM in many studies in the literature [ 152 ].…”
Section: Vascular Mimicry As a Distinct Angiogenic Mechanism In Bladd...mentioning
confidence: 99%